Management Approaches to Radical Social Media Activism: the responses of BP, HSBC and Nestlé to Greenpeace - Grant, Bettina (2010)
Corporate directed radical activism has been reframed by the internet and social media, which provide radical activists with new tools to mount innovative attack forms against corporations. These attack forms (herein termed by author as radical social media activism) happen in the digital sphere and augment radical attack forms in the physical world. Corporations are challenged with a new age of radical activism and, thus far, have displayed low competence at using social media to manage this threat, which creates reputation and legitimacy risks. In seeking to understand current management approaches to radical social media activism, this report explores the responses of BP, HSBC and Nestlé to radical social media attacks from the environmental activist group, Greenpeace. Whilst acknowledging that the three corporations each adopted different engagement strategies to manage the Greenpeace attacks, it is argued that these engagement strategies more or less differ from the corporations’ approaches to managing radical activism in the physical world, yet the principles for managing corporate directed radical activism in any sphere are the same. Furthermore, in noting that parallels exist between managing radical social media activism and managing radical activism in the physical world, it is suggested that corporations are looking to conventional crisis management models and engagement strategies to address this relatively new threat. It is further argued that corporations electing not to engage with radical social media activists need not experience short run disadvantage, and that alternative approaches may at times better serve the corporation. Moreover, the report suggests that radical social media activism has redrawn how corporations engage with non-market issues, yet not recast the corporation-radical activist dynamic.